(untitled) (Journal of Informatics Education and Research, 2025)
The study’s aim was to find the impact of eWOM (electronic word of mouth) as quality, quantity, & credibility reviews on the purchase intention of Korean products among Indian customers in Uttar Pradesh, India. The study employed an exploratory as well as descriptive research design. A web based structured Google form questionnaire is used to get the primary data. In the preliminary pilot study, the study employed Cronbach’s alpha, Bartlet test of significance, % of variance and Kaiser-Meyer-Olkin (KMO) test value under the reliability and validity of the structured questionnaire. The study used Principal Component Analysis (PCA) for the extraction/ component matrix. The sample size was 407. The study employed correlation as well as regression enter method to test the cause-and-effect relationship and hypothesis testing among triadic review constructs of eWOM. The study’s results concluded that there was a significant impact of eWOM as quality, quantity, and credibility reviews on the purchase intention. The quality, quantity, and credibility of the electronic word of mouth reviews had the significant effect on the purchase intention. The results of eWOM reviews helped the companies in designing the e-commerce strategies on social media platforms. The study helped the marketers while choosing the best content strategies, celebrity partnerships, and customer interaction methods for Indian customers. The study helped the Indian customers while purchasing Korean products based on the eWOM reviews in Uttar Pradesh, India.